2015
DOI: 10.1094/phyto-05-15-0129-r
|View full text |Cite
|
Sign up to set email alerts
|

Metalaxyl Resistance in Phytophthora infestans: Assessing Role of RPA190 Gene and Diversity Within Clonal Lineages

Abstract: Prior work has shown that the inheritance of resistance to metalaxyl, an oomycete-specific fungicide, is complex and may involve multiple genes. Recent research indicated that a single nucleotide polymorphism (SNP) in the gene encoding RPA190, the largest subunit of RNA polymerase I, confers resistance to metalaxyl (or mefenoxam) in some isolates of the potato late blight pathogen Phytophthora infestans. Using both DNA sequencing and high resolution melt assays for distinguishing RPA190 alleles, we show here t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 39 publications
(52 reference statements)
2
43
1
1
Order By: Relevance
“…Several P. infestans clonal lineages, including US‐6, 7, 8, 11 and 20, have shown resistance to Metalaxyl or Mefenoxam (Metalaxyl‐M), two of the most effective main ingredients of systemic fungicides against the pathogen. Intermediate resistance to Metalaxyl/Mefenoxam has also been observed in clonal lineages US‐21, 22, 23 (currently the most prevalent in the United States), and 24 (Chowdappa et al., ; Gevens, ; Matson, Small, Fry, & Judelson, ; Roberts, ).…”
Section: Introductionmentioning
confidence: 98%
“…Several P. infestans clonal lineages, including US‐6, 7, 8, 11 and 20, have shown resistance to Metalaxyl or Mefenoxam (Metalaxyl‐M), two of the most effective main ingredients of systemic fungicides against the pathogen. Intermediate resistance to Metalaxyl/Mefenoxam has also been observed in clonal lineages US‐21, 22, 23 (currently the most prevalent in the United States), and 24 (Chowdappa et al., ; Gevens, ; Matson, Small, Fry, & Judelson, ; Roberts, ).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, we believe that these three AA mutations (V1476G, P980S and F382Y) are essential for metalaxyl resistance. This may explain the previously inconsistent results in which only the role of the F382Y mutation was investigated . We checked the complete sequences from Matson's and Randall's studies and found all resistant isolates except for one in Matson et al .…”
Section: Discussionmentioning
confidence: 99%
“…None of the sensitive isolates carried any of these mutations, except for isolate 11016 in the Matson et al . study . We also checked isolates with the 1145 SNP (corresponding to F382Y) from both studies and found that all sensitive isolates carried a TT nucleotide except for one in the Randall et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All fungicides impose a selection pressure on their target pathogen populations, and some fungicides are prone to the development of resistance. This is especially true for fungicides with a single target site, as mutations in the target gene can lead to the selection of a resistant sub-population in the pathogen population with fungicide applications [4][5][6][7]. Some widely used examples of such fungicides include succinate dehydrogenase inhibitors (SDHIs), quinone outside inhibitors (QoIs), de-methylation inhibitors (DMIs), and phenylamides (PAs).…”
Section: Introductionmentioning
confidence: 99%